2015
DOI: 10.1016/j.jchf.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The Diastolic Pulmonary Gradient Does Not Predict Survival in Patients With Pulmonary Hypertension Due to Left Heart Disease

Abstract: Objectives To evaluate if diastolic pulmonary gradient (DPG) can predict survival in patients with pulmonary hypertension due to left heart disease (PH-LHD). Background Patients with combined post- and pre-capillary PH-LHD have worse prognosis than those with passive pulmonary hypertension. The transpulmonary gradient (TPG) and pulmonary vascular resistance (PVR) have commonly been used to identify high-risk patients. However, these parameters have significant shortcomings and do not always correlate with pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
155
3
13

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(185 citation statements)
references
References 25 publications
(45 reference statements)
13
155
3
13
Order By: Relevance
“…We have chosen a PVR of 3 WU because this usually denotes the presence of PVD in patients with PAH. Although Tampakakis et al 46 did not show additional benefit in determining prognosis when combining PVR and DPG, we believe that DPG still has strong physiological grounding and that its role should not be dismissed. This does leave us with a group of patients who have DPG ≥ 7 mmHg and PVR < 3 WU or DPG < 7 mmHg and PVR ≥ 3 WU, whose phenotype is presently unclear.…”
Section: Diagnostic Algorithmcontrasting
confidence: 54%
“…We have chosen a PVR of 3 WU because this usually denotes the presence of PVD in patients with PAH. Although Tampakakis et al 46 did not show additional benefit in determining prognosis when combining PVR and DPG, we believe that DPG still has strong physiological grounding and that its role should not be dismissed. This does leave us with a group of patients who have DPG ≥ 7 mmHg and PVR < 3 WU or DPG < 7 mmHg and PVR ≥ 3 WU, whose phenotype is presently unclear.…”
Section: Diagnostic Algorithmcontrasting
confidence: 54%
“…The exact definition of PH in the setting of left heart disease is still debated, but includes at least the criteria of a mean pulmonary artery pressure greater than or equal to 25 mmHg and a pulmonary capillary wedge pressure greater than or equal to 15 mmHg (10). Additional hemodynamic criteria of PH in the setting of left heart disease, along with how such criteria affect prevalence and outcomes, continue to be debated, with the ultimate goal to identify a phenotype amenable to specific targeted therapies (1,2,(10)(11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Recent epidemiological studies in group 2 PH focused on markers of pulmonary vascular remodeling, such as transpulmonary pressure gradient (TPG), 3-6 pulmonary vascular resistance (PVR), 3,4, 6 and diastolic pulmonary vascular pressure gradient (DPG). 5- 8 The results obtained so far, however, are controversial. Furthermore, sustained PH leads to right ventricular dysfunction, which is partly represented as elevated mean right atrial pressure (RAP).…”
Section: Editorial P 72 Methodsmentioning
confidence: 99%
“…6 In contrast, Tedford et al reported the poor prognostic ability of DPG in patients with PH due to LHD even though they used multiple cut-off points. 7, 8 Their subjects included younger patients 7, 8 and those with less coronary artery disease 8 compared with the Gerges et al study. 6 The problem is that DPG is sensitive to measurement error because the absolute value is small, and DPG is affected by many factors including lung disease, sepsis, hypoxia, acidosis, and coronary artery bypass surgery.…”
Section: Study Limitationsmentioning
confidence: 99%